Evaluación de biocatalizadores producidos utilizando CalB o células/enzimas de Yarrowia lipolytica para la síntesis de isobutil propionato en un biorreactor de lecho empacado Sólido/Gas - Cruz Martínez, Yahir Alejandro (Universidad Autónoma Metropolitana, 2025)
The enzymatic production of volatile esters has garnered significant interest across the food, cosmetic, and pharmaceutical industries. As a sustainable alternative to conventional methods (chemical synthesis and direct natural extraction), biotechnological approaches such as solid/gas biocatalysis (S/G) have emerged as promising strategies. In this system, enzymes (e.g., lipases) or whole cells exhibiting lipolytic activity are employed as biocatalysts. These must be immobilized onto a solid support and packed within a tubular reactor, where the gaseous substrates are introduced and transported via an inert carrier gas. The S/G configuration offers several advantages over conventional monophasic or biphasic systems, including enhanced conversion efficiencies, elevated space time yields, improved mass transfer dynamics, and most notably, the elimination of liquid solvents. This solvent-free operation not only facilitates the downstream recovery of both the target ester and the biocatalyst but also aligns with green chemistry principles. In this study, a gas-phase packed-bed tubular bioreactor was employed for the synthesis of isobutyl propionate (isoPro), a fruity ester characterized by a rum-like aroma and flavor. The esterification reaction was conducted using propionic acid (aciP) and isobutanol (isoB) as substrates, with nitrogen gas serving as the carrier. Three different biocatalysts were evaluated: CalB Immo Plus™ (CalB-IP), CalB/BSA crosslinked enzyme aggregates (CalB-CLEA), and immobilized cells/enzymes of the yeast Yarrowia lipolytica NRLL 7817 (Ylip), obtained via biphasic fermentation. Here, CalB denotes Candida antarctica lipase B, a widely utilized industrial enzyme available commercially in both free and immobilized forms, the latter typically supported on polymeric resins such as polymethacrylate-divinylbenzene (e.g., Novozym® 435, CalB Immo Plus™). Initial assessments of the S/G system using the commercial CalB-IP demonstrated conversion yields exceeding 97 % by increasing the molar ratio of alcohol to acid from 1:1 to 4:1 and by lowering the water activity (aw) of the biocatalyst to 0.11. These results outperformed those reported for other systems employing the same enzyme and substrates, including supercritical CO₂ and solvent-free liquid-phase reactions. Furthermore, continuous operation under steady-state conditions was sustained for up to 10 hours without significant loss in conversion efficiency. A noteworthy phenomenon of substrate–resin interaction via physical adsorption was also observed and characterized. This interaction initially limited the reaction rate but yielded valuable insights into the role of adsorption–desorption kinetics and intraparticle diffusion in determining the overall productivity of the S/G system. As an alternative to the commercial biocatalyst, the same Candida antarctica lipase B (CalB) was used in its free form and subsequently immobilized via crosslinked enzyme aggregates (CLEA) method, employing bovine serum albumin (BSA) as a co-feeder and glutaraldehyde (GA) as the crosslinking agent. This approach yielded a fully protein-based, greener, and more sustainable biocatalyst. Remarkably, CalB-CLEA exhibited approximately sixfold higher capacity per mole of enzyme (in terms of Total Turnover Number “TTN”) (12.13 ± 0.15 x 103 mol of isoPro mol-1 CalB) and a specific volumetric productivity (space time yield “STY” mg-1 CalB) fourfold higher compared to CalB-IP (0.652 ± 0.02 g isoPro L⁻¹ h⁻¹ mg-1 CalB), while maintaining conversion yields above 90 % under S/G conditions. Furthermore, it retained over 50 % of its initial activity after 25 hours of continuous operation. Contrary to observations with CalB-IP, the performance of CalB-CLEA was negatively affected by decreasing water activity (aw), with optimal conversion achieved at aw = 0.52, using a CLEA preparation containing 10 mg mL⁻¹ BSA and 3 % glutaraldehyde. Overall, the process employing CalB-CLEA not only delivered improved green metrics relative to the CalB-IP in S/G system but also outperformed the same CLEA formulation when used in organic media, highlighting its superior catalytic and environmental profile within the context of sustainable esterification technologies. Finally, whole-cell biocatalysts were obtained directly by drying the solid fractions recovered from biphasic cultures of Ylip, aiming to develop a more cost-effective alternative that circumvents the need for commercially available enzymes. The intrinsic catalytic capacity of the Ylip enzymatic machinery was demonstrated during the esterification process. Among various inert culture supports evaluated, polyurethane foam (PUF) was identified as the most effective. A cultivation time of 72 h was selected for biocatalyst recovery based on measurements of both hydrolytic and synthetic activity in organic media. Notably, substrate specificity toward medium-chain esters (particularly p-nitrophenyl octanoate C8) was observed in hydrolytic assays, and the conversion yield to isobutyl propionate in batch reactions reached approximately 20 %. In contrast, under S/G conditions, the same biocatalyst achieved only ~2 % conversion yield. Despite its lower efficiency, its main advantages lie in its potential for continuous operation and the simplicity and reproducibility of its production process. Additionally, CLEAs were synthesized directly from the crude enzymatic extract obtained after the optimized fermentation period. In this context, both BSA and another biodegradable biomolecule with a high number of reactive groups, such as chitosan, were independently evaluated as “co-feeders” during precipitation, with isoamyl alcohol proving to be the most effective precipitant for both. Immobilization with BSA yielded superior results, with immobilization efficiencies exceeding 96 % and thermal stability maintaining approximately 80 % of residual activity after 2 hours of incubation at 55 °C. These findings underscore the potential of this novel, green, and low-cost biocatalyst for future applications in S/G phase biocatalysis.; La producción de ésteres volátiles es de gran interés en la industria alimentaria, cosmética y farmacéutica. Una alternativa verde a los procesos tradicionales utilizados para su obtención (síntesis química y extracción directa de plantas o frutas), es hacer uso de procesos biotecnológicos como la biocatálisis sólido/gas (S/G). En donde se hace uso de enzimas como las lipasas o células completas con actividad lipolítica como biocatalizadores, mismos que deben encontrarse inmovilizados en un soporte sólido para ser empacado dentro de un reactor tubular por donde fluyen los sustratos en fase gaseosa con la ayuda de un acarreador. El uso del sistema S/G presenta diversas ventajas sobre otros sistemas mono o bifásicos, principalmente referentes a altos rendimientos de conversión acompañados de altas tasas de producción, así como fenómenos de transferencia de masa más eficientes y, en particular, evita el uso de solventes líquidos, lo cual brinda facilidad para recuperar el producto de interés y el mismo biocatalizador. En este proyecto se utilizó un biorreactor tubular de lecho empacado en sistema S/G para la obtención de isobutil propionato (isoPro), un éster con aroma y sabor a ron “afrutado”. Su síntesis se llevó a cabo utilizando ácido propiónico (aciP) e isobutanol (isoB) como sustratos y nitrógeno como gas acarreador. Para ello, se evaluaron tres biocatalizadores: CalB Immo PlusTM (CalB-IP), crosslinked enzyme aggregates de CalB con BSA (CalB-CLEA) e inmovilizados de células/enzimas de la levadura Yarrowia lipolytica NRLL 7817 (Ylip) obtenidos mediante fermentación bifásica. En este contexto, CalB hace referencia a la lipasa B de Candida antárctica, enzima de importancia industrial que se puede encontrar en el mercado de forma libre o inmovilizada en resinas poliméricas como la de polimetacrilato-divinilbenceno (Ej. Novozym 435®, CalB Immo PlusTM). En primera instancia, al evaluar el sistema S/G con el producto comercial CalB-IP se logró alcanzar rendimientos de conversión > 97 % al incrementar la relación molar de 1:1 a 4:1 (alcohol:ácido respectivamente) y disminuir a 0.11 el valor de aw del catalizador, ese porcentaje de conversión fue superior a lo reportado en otros sistemas de reacción (CO2 supercrítico y libre de solventes) basados en el mismo producto y enzima, logrando además, trabajar de forma continua durante 10 h manteniendo la producción en estado estacionario a dicho nivel de conversión. En este mismo apartado, se identificó y elucidó un importante fenómeno de interacción vía adsorción física entre los sustratos y la resina polimérica, lo cual limitó la velocidad inicial de reacción durante los ensayos, pero que brindó información sumamente relevante sobre el papel del tiempo característico de adsorción-desorción de sustratos/productos y los mecanismos de difusión intrapartícula, en las tasas de producción en sistema S/G. Por otro lado, se buscaron alternativas a dicho biocatalizador comercial utilizando CalB e inmovilizándola mediante el método de agregados enzimáticos entrecruzados (CLEA: por sus siglas en inglés de crosslinked enzyme aggregates) junto con seroalbúmina bovina (BSA) y glutaraldehído (GA) como agente entrecruzante, dando como resultado un biocatalizador más verde y sostenible, debido a su naturaleza totalmente proteica, lo que resultó en una productividad (total turnover number “TTN”) en sistema S/G aproximadamente seis veces superior a CalB-IP por cada mol de enzima utilizada (12.13 ± 0.15 x 103 mol de isoPro mol-1 CalB) y un valor promedio de productividad volumétrica específica (space time yield “STY” mg-1 CalB) 4 veces superior (0.652 ± 0.02 g isoPro L⁻¹ h⁻¹ mg-1 CalB), con rendimientos de conversión >90 %, sin perder < 50 % de dicha actividad tras 25 h de uso. A diferencia de lo obtenido con CalB-IP se observó un efecto negativo de la disminución del valor de aw, encontrando los mejores rendimientos con aw 0.52 y el tratamiento con 10 mg mL-1 BSA - 3 % GA. En el sentido general, se obtuvo un proceso más sostenible y eco-amigable tras obtener métricas másicas de verdor superiores a las obtenidas con CalB-IP y con la misma CalB-CLEA en medio orgánico, mostrando superioridad tanto a nivel de sistema catalítico como de biocatalizador respecto a los sistemas alternativos mencionados anteriormente. Además, se probaron biocatalizadores obtenidos directamente del secado de los sólidos recuperados de cultivos bifásicos de Ylip, logrando identificar la capacidad de su maquinaria enzimática en el mismo proceso de síntesis, en la búsqueda de un proceso más rentable, al evitar la necesidad de adquirir una enzima comercial. Se identificó la superioridad de la espuma de poliuretano (PUF) como soporte inerte para los cultivos; 72 h de cultivo fue el tiempo seleccionado para recuperar los biocatalizadores tomando como criterio la actividad de hidrólisis y síntesis en medio orgánico. Afín a esto, se observó especificidad por sustratos de cadena mediana C8 (p-NPOc) al cuantificar su actividad hidrolítica y rendimientos de conversión a isobutil propionato de ~ 20 %. En contraparte, sólo se alcanzó un rendimiento de conversión de ~ 2 % en sistema S/G. Aunque es un valor relativamente bajo, se tiene como principal ventaja la capacidad de trabajar en continuo y la relativamente fácil obtención del biocatalizador. Finalmente, se produjeron CLEAs utilizando directamente el extracto crudo obtenido tras el tiempo de fermentación mencionado. En este sentido, se evaluaron de forma independiente la BSA y otro biopolímero biodegradable con alta densidad de grupos funcionales reactivos, el quitosano (Q); como agentes protectores o co-feeders, identificándose al alcohol isoamílico como el precipitante más eficaz en presencia de ambos materiales. Siendo la BSA con la que se obtuvieron los mejores rendimientos de inmovilización (> 95 %) y termorresistencia (~ 80 % de actividad recuperada tras 2 h a 55 °C). En este sentido, se obtuvo una novedosa alternativa de biocatalizador verde y rentable para ser evaluada en un futuro en el sistema biocatalítico S/G.